2016
DOI: 10.1016/j.plabm.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of different methodologies to detect the JAK2 V617F mutation in chronic BCR-ABL1 negative myeloproliferative neoplasms

Abstract: ObjectivesA mutation in the JAK2 gene, V617F, has been identified in several BCR-ABL1 negative myeloproliferative neoplasms (MPN): polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF). Defining the presence or absence of this mutation is an essential part of clinical diagnostic algorithms and patient management. Here, we aimed to evaluate the performance of three PCR-based assays: Amplification Refractory Mutation System (ARMS), High-Resolution Melting analysis (HRM), and San… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…In their combined measurement, an OR of 3.5 was obtained (95% CI = 1.6–7.7). Eight studies used the WHO 2008 criteria [41, 4851, 54, 62, 66], for which an OR of 4.7 (95% CI = 3.1–7.5) was found. Three studies used WHO 2008 criteria and AS-PCR, and their combined measurement was an OR of 3.8 (95% CI = 1.6–8.3).…”
Section: Resultsmentioning
confidence: 99%
“…In their combined measurement, an OR of 3.5 was obtained (95% CI = 1.6–7.7). Eight studies used the WHO 2008 criteria [41, 4851, 54, 62, 66], for which an OR of 4.7 (95% CI = 3.1–7.5) was found. Three studies used WHO 2008 criteria and AS-PCR, and their combined measurement was an OR of 3.8 (95% CI = 1.6–8.3).…”
Section: Resultsmentioning
confidence: 99%
“…Applied to ddPCR, LoD could be defined as the smallest number of target nucleic acid molecules that is statistically distinguishable from the background or negative control. One approach for estimating LoD and LoB for a ddPCR assay has been experimentally demonstrated in a study to determine lower limits of detection for cancer-related mutations [33,34]. As is well-known, accurate quantification of nucleic acid molecules by ddPCR is based on the correct sorting of single droplets into negative and positive populations, since the proportion of positive partitions is an integral component of the equation used to determine copy number concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on NAT2 gene among Jordanians genotyped major NAT2 genetic polymorphisms using the PCR-RFLP method [11,28]. It has been reported that DNA sequencing is the golden method for genotyping [29], while the PCR-RFLP technique has large errors with a higher probability of false-positive results [30]. Some studies have found that the PCR-RFLP technique is less accurate than other genotyping assays, such as direct DNA sequencing and pyrosequencing [31–33].…”
Section: Discussionmentioning
confidence: 99%